2023
DOI: 10.1001/jamanetworkopen.2023.3012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Area Deprivation With Primary Hypertension Diagnosis Among Youth Medicaid Recipients in Delaware

Abstract: ImportanceThe association between degree of neighborhood deprivation and primary hypertension diagnosis in youth remains understudied.ObjectiveTo assess the association between neighborhood measures of deprivation and primary hypertension diagnosis in youth.Design, Setting, and ParticipantsThis cross-sectional study included 65 452 Delaware Medicaid-insured youths aged 8 to 18 years between January 1, 2014, and December 31, 2019. Residence was geocoded by national area deprivation index (ADI).ExposuresHigher a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Individual research and publications use the ADI in studies on chronic conditions to great effect, such as the study which recently found that in Delaware Medicaid recipients between the ages of 8 and 18 “communities with ADI greater than or equal to 50 was associated with 60% greater odds of a hypertension diagnosis.” 15 However, at the enterprise level, health systems and insurers alike are slow to take on the cost and effort associated with a comprehensive geocoding strategy that would allow rapid iterations of these kinds of analysis within chronic disease management programs.…”
Section: Moving Medical Data From Simple Demographics To Population D...mentioning
confidence: 99%
“…Individual research and publications use the ADI in studies on chronic conditions to great effect, such as the study which recently found that in Delaware Medicaid recipients between the ages of 8 and 18 “communities with ADI greater than or equal to 50 was associated with 60% greater odds of a hypertension diagnosis.” 15 However, at the enterprise level, health systems and insurers alike are slow to take on the cost and effort associated with a comprehensive geocoding strategy that would allow rapid iterations of these kinds of analysis within chronic disease management programs.…”
Section: Moving Medical Data From Simple Demographics To Population D...mentioning
confidence: 99%
“…2 With the changing landscape of atherosclerosis that has shifted to developing countries, women, and younger individuals, current knowledge gaps include an incomplete understanding of (1) sex differences in CVD in CKM syndrome, (2) genetic underpinnings of disease that may account for some regional differences and clinical applications of genetic testing, (3) mechanisms of endothelial dysfunction in CKM syndrome (accelerated in the presence of CKD 42 ) as an early harbinger of CVD, and (4) environmental and community-level risk factors in the development of CVD. 43 In contrast to atherosclerosis, mechanisms by which CKM syndrome leads to HF and arrhythmias (and, in particular, atrial fibrillation [AFib]) are less well described. Adiposity itself leads to hemodynamic changes.…”
Section: Mechanisms Of Cvd Development In Ckmmentioning
confidence: 99%
“…Higher area deprivation is associated with greater odds of a hypertension diagnosis among youth. According to a cross-sectional analysis of 65 452 Delaware Medicaid recipients, 8–18 years of age, patient level factors associated with greater odds of a hypertension diagnosis were obesity diagnosis (OR 5.16; 95% CI, 4.54–5.85), older age (1.16; 95% CI, 1.14–1.18), and ADI greater than or equal to 50 (OR 1.61; 95% CI, 1.04–2.51), the state's upper quartile cutoff [30 ▪ ].…”
Section: Association Of Neigborhood Deprivation With Obesity and Rela...mentioning
confidence: 99%